Antibacterial activity of dali ni horbo protein extract modified with citrus and pineapple juice - Tesa, Catrin Angelica Putri; Razoki, Razoki; Piska, Finna (Buletin Kedokteran & Kesehatan Prima, 2026)
Background: The global rise in antibiotic resistance highlights the urgent need to identify novel, natural antimicrobial agents. Fermented dairy products represent potential sources of bioactive peptides with inherent antibacterial properties. Dali ni horbo is a traditional fermented buffalo milk product from North Sumatra, Indonesia. This study aimed to evaluate the in vitro antimicrobial activity of a crude protein extract from dali ni horbo, modified with orange and pineapple juice, against selected pathogenic microorganisms. Methods: This experimental laboratory study employed disk diffusion and well diffusion methods on agar media to assess the extract’s activity against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Propionibacterium acnes, and Candida albicans. Results: The results showed no inhibition zones for any treatment against all tested microorganisms. The absence of detectable antimicrobial activity may be attributed to the low concentration or biological activity of antibacterial compounds in the crude extract, the possible degradation of bioactive peptides during extraction, and the limited diffusion capacity of high‑molecular‑weight proteins in solid agar media. Conclusion: In conclusion, under the experimental conditions and methods applied, the crude protein extract of dali ni horbo did not exhibit antimicrobial activity against the tested bacterial and fungal species. Further studies involving protein purification, bioactive peptide isolation, and alternative liquid-based susceptibility assays are recommended.